Assessment of Family Medicine Obstetrics Fellowship Websites in the United States: Content and Usability - Robert Owens; T. Carl Whittaker; Annie Galt; Saskia Spiess; Matthew Mervis; Alex Lockrey; Elena Gardner; Kirsten Stoesser; Dominik Ose (SAGE Publishing, 2024)
Introduction: The United States is experiencing maternity care shortages. Family physicians can play a role in addressing these shortages. Family medicine obstetrics fellowships train family physicians in obstetrics care. Fellowship websites are important for promoting programs and attracting applicants. However, whether websites provide sufficient program information is unknown. This study aimed to assess completeness and utility of family medicine obstetrics fellowship websites across the United States. Method: The study analyzed 46 family medicine obstetrics fellowship websites. The component analysis evaluated the presence of 17 components related to orientation, curriculum, program, personnel, and additional content. The qualitative analysis included ratings for navigation and application, information quality, and esthetics. Analysis included percentages for websites and components and average qualitative ratings. Results: Common components included overviews, training requirements, and contact information. Description of the patient population was the least common component. Usability ratings varied across programs, with higher ratings observed for navigation and application, and information quality. Esthetics and visual appeal received lower ratings. Regional analysis indicated that websites from fellowships in the West and Southwest tended to include more components compared to those in the Southeast. Discussion: Family medicine obstetrics fellowship websites serve as valuable sources of program information for prospective applicants. However, not all websites include essential program details. Some information is rarely provided. Given the shortage of maternity care providers, it is crucial to develop informative and functional websites to attract applicants. Improving website content and design could prove to be a cost-effective strategy to increase the number of applicants.